2014
DOI: 10.1590/s1414-753x2014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Influência de fatores ambientais na distribuição de famílias de insetos aquáticos em rios no sul do Brasil

Abstract: Os rios neotropicais sofrem os efeitos das ações humanas. Medidas conservacionistas, pela escassez de estudos na região e do conhecimento límnico, baseiam-se em dados referentes a outras regiões, sendo muitas vezes ineficazes pela inobservância das diferenças nas respostas das comunidades aquáticas às variáveis ambientais em escalas distintas. Este estudo teve como objetivos: conhecer a riqueza de insetos aquáticos em uma bacia neotropical; verificar qual a influência das variáveis ambientais na distribuição d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
(48 reference statements)
0
5
0
3
Order By: Relevance
“…Other studies carried out in southern Brazil indicated a lower taxa representativeness (Bueno et al 2003;Pereira and De Luca 2003;Ayres-Peres et al 2006;Strieder et al 2006a;Buckup et al 2007;Milesi et al 2009 ;Biasi et al 2010;Sobczack et al 2013;Baptista et al 2014;Salvarrey et al 2014). The study conducted the closest to our study area was carried out in the Ibicuí River basin, west of Rio Grande do Sul, also within the Pampa biome (Baptista et al 2014). These authors sampled more than 9,000 individuals, distributed in 26 aquatic insect families, in the evaluated streams.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies carried out in southern Brazil indicated a lower taxa representativeness (Bueno et al 2003;Pereira and De Luca 2003;Ayres-Peres et al 2006;Strieder et al 2006a;Buckup et al 2007;Milesi et al 2009 ;Biasi et al 2010;Sobczack et al 2013;Baptista et al 2014;Salvarrey et al 2014). The study conducted the closest to our study area was carried out in the Ibicuí River basin, west of Rio Grande do Sul, also within the Pampa biome (Baptista et al 2014). These authors sampled more than 9,000 individuals, distributed in 26 aquatic insect families, in the evaluated streams.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies indicate that aquatic macroinvertebrate communities show gradual changes in species richness and composition along the longitudinal dimension as not only the stream order and composition but also habitat complexity increase, giving rise to nested patterns composition or variations in macroinvertebrate functional groups (Pereira and De Luca 2003;Milesi et al 2009;Baptista et al 2014). In rivers with large longitudinal variation in climate, geology, substrate and relief, community assemblage generally shows strong discontinuities with high species turnover between adjacent sites (Bagatini et al 2012;Barbero et al 2013;Mc Conigley et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the type of substrate could partially explain the lower diversity found in TIB streams. Texture, compaction, and grain size can affect the composition and abundance of benthic macroinvertebrates (Nakamura & Kikuchi, 1996;Fidelis, Nessimian, & Hamada, 2008;Baptista et al, 2014). Sandy soils are characterized by low heterogeneity and availability of physical habitats (Allan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Physical, chemical and structural features are also important for aquatic life; for instance, dissolved oxygen, electric conductivity, alkalinity, and temperature are known to influence invertebrate occurrence and distribution (Melo, 2009;Rezende et al, 2014). Additionally, the communities' composition changes and the richness increase from the headwaters to the base level in response mainly to stream's width, depth, temperature and production/respiration ratio (Vannote et al, 1980;Jacobsen, 2004;Baptista et al, 2014).…”
mentioning
confidence: 99%
“…Portanto, a Teoria Hierárquica de Manchas parece funcionar melhor em córregos tropicais do que a Teoria do Rio Contínuo, ao explicar a diversidade de presas e predadores da fauna de EPTOH em riachos de cabeceiras. Esses resultados são condizentes com as observações de Oliveira & Nessimian (2010), Shimano et al, (2012) e Baptista et al, (2014), onde os tipos de substratos são preditores da abundância e riqueza de macroinvertebrados bentônicos (incluindo presas e predadores), pois influenciam a estrutura dos habitats, podendo determinar a ocorrência e a diversidade das espécies. O modelo hierárquico de manchas também explicou a distribuição de grupos de alimentação funcionais em ambientes lóticos menores (cachoeiras) (Brasil et al, 2014).…”
Section: Discussionunclassified